ONSET OF DEMENTIA SYMPTOMS AFTER CESSATION OF SMOKING: A CASE REPORT - Demir, Caner F.; Ozdemir, Hasan H. (Elsevier Science Inc, 2014)
[Abstract Not Available]
6th International Conference on Alzheimers Disease and Related Disorders in the Middle East -- OCT 25-27, 2013 -- Istanbul, TURKEY